SCHOOL BASED MANAGEMENT AT PONDOK PESANTREN LA TANSA LEBAK BANTEN - Riri Suprihatin; Makruf Akbar; Yetti Supriyati (Program Pascasarjana Universitas Negeri Jakarta, 2017)
Pesantren is one of a model of Islamic education in Indonesia to continue to exist until now, thus remain interesting to study. Pesantren future must be able to compete with other educational institutions to restructure management in line with the development and needs of the times. This article peeling pattern implementation of school based management (SBM) in PondokPesantren La TansaLebakBanten.With the case study method that takes the focus of School-Based Management (SBM), researchers found that, (1) the curriculum management that integrated curriculum between the Curriculum Department of Education and Curriculum Pesantren; (2) the management of educators, (3) the student management is divided into two channels, namely 'teaching path' and 'parenting path' (4) the financial management is managed by LKMS La TansaMandiri, (5) the management of facilities and infrastructure, (6) the school and community relationship management, (7) the management of special services include; libraries, laboratories, health, dormitories, boarding schools and business units, and (8) the management of monitoring and evaluation is forming the a special team in which includes principals, teachers council, and the teaching section. All the management mentioned above is managed through the implementation of School-Based Management (SBM). Keywords:School based management (SBM), curriculum, educators, students, finance, facilities and infrasctructure, school and communityrelations, special services, and monitoring andevaluation